2017
DOI: 10.1111/jpn.12658
|View full text |Cite
|
Sign up to set email alerts
|

Clinical nutrition counselling service in the veterinary hospital: retrospective analysis of equine patients and nutritional considerations

Abstract: SummaryNutrition plays a very important role in the healthy and in the ill horse. Although research in this field clearly shows that incorrect nutritional practices may lead to severe pathologies, inappropriate feeding plans often continue to be used. A clinical nutrition counselling (CNC) service could thus be of great use to both horse owners and veterinarians. The aim of this study was to provide information on equine patients referred to the CNC service of the University of Turin and to provide standard di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…In horses, VLDL is the major transporter of triglycerides and contains about 57% triglycerides and 15% phospholipids (Watson et al, 1993). Thus, the elevation of VLDL occurs concomitantly with that observed with triglycerides, corroborating the data obtained in this study, since VLDL is the main transporter of triglycerides in horses.…”
Section: Arqsupporting
confidence: 91%
See 2 more Smart Citations
“…In horses, VLDL is the major transporter of triglycerides and contains about 57% triglycerides and 15% phospholipids (Watson et al, 1993). Thus, the elevation of VLDL occurs concomitantly with that observed with triglycerides, corroborating the data obtained in this study, since VLDL is the main transporter of triglycerides in horses.…”
Section: Arqsupporting
confidence: 91%
“…The observed HDL activity agrees with the results of Bauer et al (1990) in a group of ponies subjected to food deprivation. Watson et al (1993) demonstrated that HDL corresponds to 61%, VLDL 24% and LDL 15% of the lipoproteins in healthy horses that are not deprived of food, not being influenced by food restriction in their serum activity. In horses, most plasma cholesterol is in HDL, unlike in humans where most of it is found in the VLDL and LDL fractions (Ileri-Büyükoglu and Güldür, 2005).…”
Section: Arqmentioning
confidence: 97%
See 1 more Smart Citation
“…Taking Equation (1) as an example, the prediction error when feeding a horse of 500 kg body weight undergoing light exercise would translate into 1 kg weight loss every 10 days if fed a low energy diet, or 1 kg weight gain every 16 days if fed a high energy diet [17]. Such errors could deviate body weight and body condition score from ideal values and negatively affect horse health and performance in the medium term [36], and should be taken into account in specialized equine nutrition counseling [37]. Nevertheless, it is worth mentioning that in the 18 mixed feeds and diets whose digestible energy was within one standard deviation of the mean (which corresponded to a crude fiber content between 16.5 and 28.5% dry matter), the mean error of estimation would be reduced to 4.77 ± 3.51% and 5.30 ± 4.06% with Equations ( 1) and ( 2), respectively, or approximately ±120 kcal/kg dry matter.…”
Section: Performance Of the Equationsmentioning
confidence: 99%
“…In fact, sport horses in particular are often fed diets rich in cereal‐based complementary feeds coupled with reduced availability of forage (Henderson, 2007; Raspa et al, 2022). This type of feeding practice could be linked to the deep‐rooted beliefs on feeding management of sport horses that persist amongst some stable managers and owners (Harris, 1999), but it could also be a consequence of reduced nutritional understanding amongst veterinarians, who are often the first source of advice (Vergnano et al, 2017). Such feeding regimens increase the risk of gastrointestinal problems and may be associated with the development of stereotypies (Durham, 2009; Hothersall & Nicol, 2009).…”
Section: Introductionmentioning
confidence: 99%